In-depth molecular and phenotypic characterization in a rice insertion line library facilitates gene identification through reverse and forward genetics approaches - Lorieux, Mathias; Blein, Mélisande; Lozano, Jaime; Bouniol, Matthieu; Droc, Gaëtan; Diévart, Anne; Périn, Christophe; Mieulet, Delphine; Lanau, Nadege; Bès, Martine; Rouvière, Claire; Gay, Céline; et al. (Wiley, 2012)
We report here the molecular and phenotypic features of a library of 31 562 insertion lines generated in the model japonica cultivar Nipponbare of rice (Oryza sativa L.), called Oryza Tag Line (OTL). Sixteen thousand eight hundred and fourteen T‐DNA and 12 410 Tos17 discrete insertion sites have been characterized in these lines. We estimate that 8686 predicted gene intervals—i.e. one‐fourth to one‐fifth of the estimated rice nontransposable element gene complement—are interrupted by sequence‐indexed T‐DNA (6563 genes) and/or Tos17 (2755 genes) inserts. Six hundred and forty‐three genes are interrupted by both T‐DNA and Tos17 inserts. High quality of the sequence indexation of the T2 seed samples was ascertained by several approaches. Field evaluation under agronomic conditions of 27 832 OTL has revealed that 18.2% exhibit at least one morphophysiological alteration in the T1 progeny plants. Screening 10 000 lines for altered response to inoculation by the fungal pathogen Magnaporthe oryzae allowed to observe 71 lines (0.7%) developing spontaneous lesions simulating disease mutants and 43 lines (0.4%) exhibiting an enhanced disease resistance or susceptibility. We show here that at least 3.5% (four of 114) of these alterations are tagged by the mutagens. The presence of allelic series of sequence‐indexed mutations in a gene among OTL that exhibit a convergent phenotype clearly increases the chance of establishing a linkage between alterations and inserts. This convergence approach is illustrated by the identification of the rice ortholog of AtPHO2, the disruption of which causes a lesion‐mimic phenotype owing to an over‐accumulation of phosphate, in nine lines bearing allelic insertions.